Epidemiology of malaria and anemia in high and low malaria-endemic North-Eastern districts of India - Hari Shankar; Hari Shankar; Mrigendra Pal Singh; Syed Shah Areeb Hussain; Sobhan Phookan; Kuldeep Singh; Neelima Mishra (Frontiers in Public Health, 2022)
Anemia and malaria are the two major public health problems that lead to substantial morbidity and mortality. Malaria infection destroys erythrocytes, resulting in low hemoglobin (Hb) levels known as anemia. Here we report the determinants of anemia in high and low malaria-endemic areas that would help understand which parasite densities, age, and gender-associated low Hb levels. Therefore, a cross-sectional mass survey (n = 8,233) was conducted to screen anemia and malaria in high and low malaria-endemic districts (HMED and LMED) of North-East India. Axillary body temperature was measured using a digital thermometer. The prevalence of anemia was found to be 55.3% (4,547/8,233), of which 45.1% had mild (2,049/4,547), 52.1% moderate (2,367/4,547) and 2.9% had severe anemia (131/4,547). Among anemic, 70.8% (3,219/4,547) resided in LMED and the rest in HMED. The median age of the anemic population was 12 years (IQR: 7–30). Overall, malaria positivity was 8.9% (734/8,233), of which HMED shared 79.6% (584/734) and LMED 20.4% (150/734) malaria burden. The village-wise malaria frequency was concordant to asymptomatic malaria (10–20%), which showed that apparently all of the malaria cases were asymptomatic in HMED. LMED population had significantly lower Hb than HMED [standardized beta (β) = −0.067, p < 0.0001] and low-density Plasmodium infections had higher Hb levels than high-density infections (β = 0.113; p = 0.031). Women of reproductive age had higher odds for malaria (OR: 1.42; 95% CI: 1.00–2.05; p = 0.04). Females (β = −0.193; p < 0.0001) and febrile individuals (β = −0.029; p = 0.008) have shown lower Hb levels, but malaria positivity did not show any effect on Hb. Young children and women of reproductive age are prone to anemia and malaria. Although there was no relation between malaria with the occurrence of anemia, we found low-density Plasmodium infections, female gender, and LMED were potential determinants of Hb.